(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2024)
This descriptive study determined the health-related quality of life (HRQoL) of 62 medical front liners (nurses, therapists, radiologic technologists, and nutritionist- dietitians) in one Philippine tertiary hospital during the COVID-19 pandemic. The researcher-made questionnaire, both expert-validated and pilot-tested, and personally administered to the respondents following health and safety protocols, was divided into two (2) parts. Part I dealt with the respondents’ profile in terms of age, gender, occupation, work shift, and length of service while Part II consisting of 23 indicators measured the respondents’ HRQoL in terms of physical, social, and psychological functioning, economic status, and dietary pattern. Descriptive statistics like percentage and weighted mean was used for the respondents’ profile and HRQoL while t-test and Kruskal-Wallis test were used for the difference in the respondents’ HRQoL relative to their profile. Results revealed that majority of the respondents aged 28 and above, were female, working as nurses, had an average work experience of 1-5 years and were assigned to the morning shift. Overall, the respondents’ HRQoL is low in all of its dimensions except for social functioning, having the economic dimension receiving the lowest score. Test of difference showed that male respondents who earned more than female respondents had better HRQoL while radiologic technologists had a better HRQoL compared to other occupations. As a whole, results imply that the quality of life of medical front liners has been affected by the pandemic but they still demonstrate strong resilience and adaptability especially for social dimension of their job since their profession requires constant human interactions and engagement. An action plan was proposed to help improve respondents’ HRQoL especially for the dimensions which received low scores